EDUKASI DAGUSIBU KEPADA KADER PKK DI WILAYAH PANYILEUKAN DAN CIBIRU ASRI BANDUNG - Rachmawati, Winasih (Buletin Udayana Mengabdi, 2020)
Self-medication is mostly done by the community to deal with complaints or symptoms of the disease by buying drugs at drug store or pharmacy.  Such treatment needs to be done appropriatel  so that people need clear information in determining the type and amount of drugs used rationally and how to use them correctly. To improve the knowledge of the community, it is necessary to conduct socialization and education of government programs regarding Dapatkan Gunakan Simpan dan Buang (DAGUSIBU). With this program, it is expected that it can be applied to communities around the campus to be able to use and store good medicines. This program was held in September-December 2018 at the Citra Panyileukan and Cibiru Asri in Bandung. The activity begins with the creation of information media, knowledge surveys to PKK cadres, cadre training, DAGUSIBU education to the community, evaluation and preparation of final reports. The results of the education are known to have increased public knowledge of the DAGUSIBU program.   Keywords : dagusibu, drugs, education